Sustainable cultivation of the white truffle (Tuber magnatum) requires ecological understanding - Čejka, Tomáš; Trnka, Miroslav; Büntgen, Ulf (Mycorrhiza, 2023)
The white truffle (Tuber magnatum Picco.; WT) is the most expensive and arguably also the most delicious species within the genus Tuber. Due to its hidden belowground life cycle, complex host symbiosis, and yet unknown distribution, cultivation of the enigmatic species has only recently been achieved at some plantations in France. A sustainable production of WTs under future climate change, however, requires a better ecological understanding of the species' natural occurrence. Here, we combine information from truffle hunters with a literature review to assess the climatic, edaphic, geographic, and symbiotic characteristics of 231 reported WT sites in southeast Europe. Our meta-study shows that 75% of the WT sites are located outside the species' most famous harvest region, the Piedmont in northern Italy. Spanning a wide geographic range from ~ 37° N in Sicily to ~ 47° N in Hungary, and elevations between sea level in the north and 1000 m asl in the south, all WT sites are characterised by mean winter temperatures > 0.4 °C and summer precipitation totals of ~ 50 mm. Often formed during past flood or landslide events, current soil conditions of the WT sites exhibit pH levels between 6.4 and 8.7, high macroporosity, and a cation exchange capacity of ~ 17 meq/100 g. At least 26 potential host species from 12 genera were reported at the WT sites, with Populus alba and Quercus cerris accounting for 23.5% of all plant species. We expect our findings to contribute to a sustainable WT industry under changing environmental and economic conditions.
Keywords: symbióza; Mycorrhizae; Global warming; Non-woody forest products; Fungi; Ascomycota; Environmental change; Symbiosis; Truffle cultivation; půda; mykorhiza; Ectomycorrhiza; Soil